Determinants and benefits of using smartphone-based information for vegetable production and marketing: a case of Lao farmers. Issue 7 (3rd October 2022) - Bounkham, Phonedalom; Ahmad, Mokbul Morshed; Yaseen, Muhammad
ABSTRACT: This paper empirically investigates the determinants of using smartphone-based agricultural information provided by the government. The study collected data through a field survey involving 130 vegetable farmers in the Vientiane Province of Lao PDR. The regression model results indicated that farmers' innovativeness, literacy of ICT tools, income share from farming, farm size, farmer age, and education were significant determinants of using government-provided smartphone-based information. The findings further revealed that the information received through smartphones helped farmers improve their vegetable production and marketing practices and increased vegetable yield and profit. The findings have implications for information developers, providers, and policymakers.